Black race as an independant risk factor for preeclampsia - Moreno, Zoila (2015)
Introduction: It is possible that black race by itself would not be a risk factor for developing preeclampsia, but an indicator of other features. Black race is associated with poverty, malnutrition, hypertension, obesity and inadequate prenatal care. Objective: To determine black race as an independent risk factor for preeclampsia. Design: Observational case control prospective study. Setting: Dos de Mayo National Hospital and Maternal Perinatal Institute, Lima, Peru. Participants: Preeclamptic and normotensive pregnant women. Interventions: A standardized interview was applied to 338 preeclamptic pregnant women and 338 normotensive pregnant women, with a total population of 676. Black race was determined by both her phenotype and her report on ancestry racial characteristics. Association between black race and preeclampsia was determined using logistic regression. Main outcome measures: Association between black race and preeclampsia. Results: Preeclampsia was more frequent in women with previous preeclampsia (OR 12.9; 95% CI 5.1-32.2), obesity before pregnancy (OR 2.2; 95% CI 1.3-3.6), 35 years of age or older (OR 2.5; 95% CI 1.4-4.6) and black phenotype or report of black parents or grandparents (OR 2.21; 95% CI 1.0-5.1); the latter association was marginal (p=0.047). Conclusions: Black race was an independent risk factor for preeclampsia. It is suggested that women with this characteristic be carefully observed and informed in order to decrease the incidence and complications of preeclampsia.